William Stanley Jevons : a lógica e a economia na revolução marginalista - Baptista, Vinícius de Souza (2016)
By studying the History of Economic Thought (HET) in undergraduate textbooks, it is clear that the treatment of the triumvirate formed by William Stanley Jevons, Léon Walras and Carl Menger shows that their ideas were homogeneous. However, when reading Jevon's main book, one realizes that there is indeed a difference of approaches and even contents between Jevons' work and, for example, Walras', as both of them agreed in their correspondence. The intention of this work is to evaluate the intellectual contribution of William Stanley Jevons to de-homogenize it from the other two main marginalists, that is, Menger and Walras. To this end, the first part of this dissertation examines Jevons' ideas on logic and methodology. His book The Principles of Science will be assessed as well since in it Jevons tried to apply his knowledge in logic to economics. In the second chapter, it is conducted a historical and economic analysis of Jevons' book The Coal Question, drawing attention to its impact on his academic life. This chapter analyzes also the role of utility in his theory of exchange and labour, which would became clear through the concepts and mathematical methods used by Jevons in his famous volume The Theory of Political Economy. The dissertation gives some emphasis too to Jevons' sunspot theory, his first attempt at analyzing economic cycles. Finally, the last chapter reviews William Jaffé's thesis on de-homogenization of the marginalist triumvirate, weighing as well the argument raised by Sandra Peart on the "re-homogenizing" of Jevons and Menger.